Matching Work Capacity and Job Demands: Toward an Enhanced Measure of Work Ability. Issue 12 (December 2015) - Noone, Jack H.; Bohle, Philip; Mackey, Martin
Abstract : Objective: The Work Ability Index (WAI), the dominant measure of work ability, provides little information for targeting workplace interventions. There are benefits of developing new measures that focus on self-rated capacity to meet job demands rather than on health subscales of the WAI. Methods: Structural equation modeling with cross-sectional data from 186 underground coal miners aged 18 to 64 years was used to model multivariate relationships between the WAI subscales, worker autonomy, and relationships with management. Results: The results show differential associations between workplace factors and the WAI subscales, particularly self-rated capacity, highlighting potential intervention avenues not identifiable using traditional composite WAI scoring. Conclusions: Focusing on self-rated work ability could be beneficial in clinical settings, provided measures are enhanced to capture a sufficient array of job demands. Abstract : Supplemental Digital Content is available in the text